Advances in Electrochromic Composite Yarns: Bridging Smart Sensors and Fashion - Tausif, M. Qamar; Naeem, Tayyaba; Fatima, Tahreem; Fatima, Noor; Noor, Mah; Israr, Laiba; Shafique, Hadia; Siddiqua, Ayesha; Anam, Amina; Chaudhary, Sabba; Maryam, Umm-e- (ACADEMIA International Journal for Social Sciences, 2026)
Smart yarns, yarns that combine sensing and color change functions in a single fabric based system, have attracted a great deal of attention in the field of smart textiles in recent years. These yarns typically consist of conductive fibers coated with electrochromic or thermochromic materials and are integrated into fabric systems that react to electrical, thermal changes or environmental parameters. In this review, smart textile systems that incorporate electrochromic (EC) composite yarns for wearable sensing and interactive textile display applications are discussed in light of recent developments. The most common sensing approaches for wearable textile systems are reviewed including temperature, pressure, gas and biochemical sensing. Fibres and yarns incorporating EC materials and related smart textile systems are overviewed in terms of materials, production methods and performance parameters including sensitivity, flexibility, response time, longevity and power consumption. Challenges encountered for EC yarns such as wash ability, environmental stability and scaling up production are discussed. Potential applications include health monitoring, safety clothing and interactive responsive fashion. This review summarizes current developments and future research avenues for developing practical, commercially viable smart textiles incorporating Electrochromic technology.